THE THERMODYNAMIC PROPERTIES OF PYRRHOTITE AND PYRITE: A RE-EVALUATION - Barker W.W.; Parks T.C. (My University, 1986)
On a plot of log sulfur activity versus inverse absolute temperature, the variation in published pyrite/pyrrhotite curves below 500°C is larger than expected from the precision of the measurements. The precise data by Rau (1976) fall between interpretations by Scott and Barnes (1971) and by Toulmin and Barton (1964) and are recommended.Scott and Barnes calibrated sulfur fugacities in the system Fe-Zn-S, against the data of Toulmin and Barton, but this involved a double extrapolation of empirical relationships, to and from a region where fugacities in pyrrhotite are unmeasured. Regular-solution models offer no improvement. An apparent interruption in the properties of the high-temperature pyrrhotite solid solution, at the composition Fe7S8 (Powell, 1983) is probably due to the inclusion of metastable microdomains of monoclinic pyrrhotite in some of Rau's experimental runs, rather than to an equilibrium change of structure. Hence, the uncertainties of extrapolation are unlikely to account for the displacement of the pyrite/pyrrhotite curve of Scott and Barnes. There may be a systematic error in the composition of pyrrhotite inferred by Scott and Barnes from X-ray lattice spacings, due to the effects of preparation-dependent ordering.Other influences on pyrrhotite thermodynamics are discussed. There is a maximum in the pyrrhotite fundamental unit-cell parameter, “a,” as composition is changed. This maximum shifts towards the Fe-rich boundary of pyrrhotite as temperature is increased, so it suggests a contribution from intrinsic defects, even at low temperatures. The thermodynamic effects of pressure need recalculating to suit these unit-cell data.